PERKEMBANGAN MOTORIK ANAK-ANAK DITINJAU DARI PERKEMBANGAN BAHASA, BERMAIN, MENGGAMBAR DAN FAKTOR-FAKTOR YANG MEMPENGARUHINYA - Nursyaidah, Nursyaidah (FORUM PAEDAGOGIK, 2016)
For searching a possible childrenâ€™s development more optimal, we need certain serious concerns and cares in balance among the following important aspects: physic, motoric, intelligence, emotion and social. The children age at the elementary school is also commonly called â€œpre-skill ageâ€. Their development tasks are learning about the various basic movement skills. Thus, we should facilitate them for approprioate condisitions in order the children are able to learn and do various motoric skills. But, as the matter of fact, some parents somewhat are lack of concerning their childrenâ€™s motoric development. In this writing, the writer tries to discuss about the importance of the childrenâ€™s motoric development, motoric development phases, and factor which is influencing them.